Total barley maiya alkaloids inhibit prolactin secretion by acting on dopamine D2 receptor and protein kinase A targets. (12th June 2021) - Gong, Xiaoyun; Tao, Jiahan; Wang, Yanming; Wu, Jinhu; An, Jing; Meng, Junhua; Wang, Xiong; Chen, Yonggang; Zou, Jili
Abstract: Ethnopharmacological relevance: Barley maiya from gramineous plants ( Hordeum vulgare L.) is obtained from ripe fruits through germination and drying. It is often used to treat diseases associated with high prolactin levels. Objective: To investigate the anti-hyperprolactinemia (anti-HPRL) mechanisms of total barley maiya alkaloids (TBMA) and hordenine. Methods: This experiment included 9 groups: Normal group, TBMA group, hordenine group, TBMA + haloperidol group, TBMA + forskolin group, TBMA + 8-bromo-cAMP group, hordenine + haloperidol group, hordenine + forskolin group, and hordenine + 8-bromo-cAMP group. The prolactin (PRL) concentration in the supernatant and the total cAMP concentration in the cells were detected by ELISA. The expression levels of PRL, dopamine D2 receptor (DRD2) and cAMP/PKA/CREB protein were measured by Western Blot. Results: In the TBMA group and the hordenine group, the PRL level in MMQ cells was significantly decreased, but in GH3 cells there was no change. DRD2 expression level was markedly increased, cAMP concentration was decreased, and the activity of PKA and CREB declined in MMQ cells. Compared with the TBMA group, there was a significant decrease of DRD2 expression level, a remarkable increase of PRL secretion and an increase of cAMP/PKA/CREB expression in MMQ cells within the TBMA + haloperidol group. Compared with the forskolin group, there was no significant change in PRL secretion and cAMP/PKA/CREB expression level in MMQ cells within the TBMA + forskolin group. There was a decrease in PRL secretion and cAMP/PKA/CREB expression level in MMQ cells within the TBMA + 8-bromo-cAMP group compared with the 8-bromo-cAMP group. Compared with the hordenine group, DRD2 expression level was significantly decreased, PRL secretion was markedly increased, and cAMP/PKA/CREB expression level was increased in MMQ cells within the hordenine + haloperidol group. There was no significant change in PRL secretion and cAMP/PKA/CREB expression level in MMQ cells within the hordenine + forskolin group compared with the forskolin group and within the hordenine + 8-bromo-cAMP group compared with the 8-bromo-cAMP group. Conclusion: TBMA and hordenine can both play an anti-HPRL role via DRD2, and TBMA can also act on PKA targets to exert its anti-HPRL effect. TBMA and hordenine may be potential treatment strategies for HPRL. Graphical abstract: Image 1